Metal-Free Mild Synthesis of Novel 1′H-Spiro[Cycloalkyl-1,2′-quinazolin]-4′(3′H)-ones by an Organocatalytic Cascade Reaction - Ramesh, Rathinam; Kalisamy, Periyathambi; Malecki, Jan Grzegorz; Lalitha, Appaswami (Synlett, 2018)
A concise organocatalytic method for the facile synthesis of some novel 1′H-spiro[cycloalkyl-1,2′-quinazolin]-4′(3′H)-ones via a one-pot, three-component condensation of isatoic anhydride, aryl or aliphatic amines and a cyclic ketone is described.
Keywords: spiro compounds; quinazolinones; isatoic anhydride; amines; cycloalkanones; multicomponent reactions